2001
DOI: 10.1136/jech.55.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analyses of neighbourhood socioeconomic context and health outcomes: a critical review

Abstract: Purpose-Interest in the eVects of neighbourhood or local area social characteristics on health has increased in recent years, but to date the existing evidence has not been systematically reviewed. Multilevel or contextual analyses of social factors and health represent a possible reconciliation between two divergent epidemiological paradigms-individual risk factor epidemiology and an ecological approach. Data sources-Keyword searching of Index Medicus (Medline) and additional references from retrieved article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

62
1,289
8
37

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,875 publications
(1,396 citation statements)
references
References 67 publications
62
1,289
8
37
Order By: Relevance
“…Other mechanisms by which an unfavorable neighborhood environment may impact health behaviors have been proposed, including a lack of access to health-promoting resources, accumulated stress brought on by the presence of hazards in the neighborhood environment, and prevailing attitudes that de-emphasize the importance of health and health behaviors. 1,12,[16][17][18][19] Because the association between neighborhood safety and adherence persisted after adjustment for multiple potential barriers to accessing a pharmacy and paying for prescriptions, including income, insurance status, and access to transportation, the lower adherence observed in unsafe neighborhoods is likely attributable to factors in addition to access and finances. It has been suggested that an accumulation of exposures to multiple unhealthy contextual factors may explain the deleterious health effects of unhealthy neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms by which an unfavorable neighborhood environment may impact health behaviors have been proposed, including a lack of access to health-promoting resources, accumulated stress brought on by the presence of hazards in the neighborhood environment, and prevailing attitudes that de-emphasize the importance of health and health behaviors. 1,12,[16][17][18][19] Because the association between neighborhood safety and adherence persisted after adjustment for multiple potential barriers to accessing a pharmacy and paying for prescriptions, including income, insurance status, and access to transportation, the lower adherence observed in unsafe neighborhoods is likely attributable to factors in addition to access and finances. It has been suggested that an accumulation of exposures to multiple unhealthy contextual factors may explain the deleterious health effects of unhealthy neighborhoods.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Individuals who live in neighborhoods perceived to be unsafe, for example, report lower levels of physical activity 21 , higher rates of smoking 22,23 , and greater levels of obesity 12 compared to individuals living in neighborhoods perceived to be safe, even after accounting for individual-level markers of socioeconomic status, such as household income. Such "neighborhood effects" on health may be particularly pronounced among individuals with type 2 diabetes, which requires consistent adherence to management regimens that are often challenging and complex.…”
Section: Introductionmentioning
confidence: 99%
“…The patient's home neighbourhood will be used as a surrogate for patient characteristics, because previous literature shows an association between home neighbourhood and cardiac risk factors, unhealthy behaviours, and overall health. [33][34][35][36][37][38][39][40][41][42][43][44][45] The neighbourhood factors of the arrest location (i.e., the pickup address) will be used to study the effects on bystander CPR, because the emergency response (i.e., bystanders and EMS/paramedics) is contingent on the arrest location. [10][11][12][13][46][47][48] A patient's home address is recorded as mailing address with street name, street number, and postal code, whereas the pickup address is recorded as a mailing address, with latitude and longitude coordinates and a Universal Transverse Mercator (UTM) value.…”
Section: Geocodingmentioning
confidence: 99%
“…Additionally, the use of multilevel statistical techniques to estimate contextual effects in health research is now widespread in the demographic literature (Rice & Jones, 1997;Duncan et al, 1998;Diez Roux, 2000;Pickett & Pearl, 2001). However, the majority of empirical studies use unweighted data even when the units present unequal selection probabilities.…”
Section: Introductionmentioning
confidence: 99%